Activated slag as partial replacement of cement mortars: Effect of temperature and a novel admixture. (20th August 2019) - Korde, Chaaruchandra; Cruickshank, Matthew; West, Roger P.; Pellegrino, Claudia
Highlights: A novel chloride free activator. Study early age strength of GGBS mortars. Compared with 0% GGBS, 0% admixture and another admixture. Study in perspective of precast industry. Abstract: This paper, from the perspective of the precast industry, reports on a study into the activation of mortar mixes with ground granulated blast furnace slag (GGBS) (0, 30, 50, 70%) and cement (CEM I 42.5R) using temperature (ambient (20 °C) and moderate (35 °C)) and accelerating admixtures (a novel chloride free activator and a commercial admixture) to enhance very early age strength. The discrete temperature activation is found to provide larger improvements in early age strength compared to the use of admixtures. However, irrespective of temperature activation, the novel admixture, in absolute terms, provides greater benefit in strength activation of GGBS mortars compared to the existing commercial admixture. Further, most of the GGBS mortar mixes equalled or surpassed the 28-day strength of the control mixes without any cross-over effects.